cAMP and cGMP signaling cross-talk: role of phosphodiesterases and implications for cardiac pathophysiology. - Zaccolo, M; Movsesian, M (2007)
Cyclic nucleotide phosphodiesterases regulate cAMP-mediated signaling by controlling intracellular cAMP content. The cAMP-hydrolyzing activity of several families of cyclic nucleotide phosphodiesterases found in human heart is regulated by cGMP. In the case of PDE2, this regulation primarily involves the allosteric stimulation of cAMP hydrolysis by cGMP. For PDE3, cGMP acts as a competitive inhibitor of cAMP hydrolysis. Several cGMP-mediated responses in cardiac cells, including a potentiation of Ca(2+) currents and a diminution of the responsiveness to beta-adrenergic receptor agonists, have been shown to result from the effects of cGMP on cAMP hydrolysis. These effects appear to be dependent on the specific spatial distribution of the cGMP-generating and cAMP-hydrolyzing proteins, as well as on the intracellular concentrations of the two cyclic nucleotides. Gaining a more precise understanding of how these cross-talk mechanisms are individually regulated and coordinated is an important direction for future research.